2021
DOI: 10.1038/s12276-021-00691-y
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of antiviral innate immune signaling and viral evasion following viral genome sensing

Abstract: A harmonized balance between positive and negative regulation of pattern recognition receptor (PRR)-initiated immune responses is required to achieve the most favorable outcome for the host. This balance is crucial because it must not only ensure activation of the first line of defense against viral infection but also prevent inappropriate immune activation, which results in autoimmune diseases. Recent studies have shown how signal transduction pathways initiated by PRRs are positively and negatively regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 357 publications
(458 reference statements)
0
28
0
Order By: Relevance
“…We do not have experimental evidence to explain this observation; however, as it has been reported that some interferon-stimulated genes activated by the type I interferon signaling pathway like ISG56 can act as negative feedback regulators of the antiviral response, one possible hypothesis could be that some variants take advantage of this negative feedback regulation and gain resistance to the antiviral activity to type I interferons response after the negative regulator is expressed. Mechanistic data comparing the evasion strategies between Flavivirus isolates could confirm the observation that Flavivirus can use multiple strategies to subvert the innate immune response of the host (Li et al, 2009;Chathuranga et al, 2021).…”
Section: Discussionmentioning
confidence: 67%
“…We do not have experimental evidence to explain this observation; however, as it has been reported that some interferon-stimulated genes activated by the type I interferon signaling pathway like ISG56 can act as negative feedback regulators of the antiviral response, one possible hypothesis could be that some variants take advantage of this negative feedback regulation and gain resistance to the antiviral activity to type I interferons response after the negative regulator is expressed. Mechanistic data comparing the evasion strategies between Flavivirus isolates could confirm the observation that Flavivirus can use multiple strategies to subvert the innate immune response of the host (Li et al, 2009;Chathuranga et al, 2021).…”
Section: Discussionmentioning
confidence: 67%
“…3B ). Many viral proteins have been demonstrated to play important roles in regulating host signaling pathways [ 13 , 28 , 29 ]. For example, the Marburg virus VP24 protein interacts with Keap1 to activate the cytoprotective antioxidative response pathway [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Active phosphorylated RIPK1 was found in epithelial cell samples from COVID-19 patients [ 62 ], and a recent study discovered that Nsp12 promotes activation of RIPK1, which in turn enhances viral replication by stimulating the expression of viral receptors, such as ACE2 and EGFR [ 63 ]. Furthermore, Nsp13 is found to limit the activation of TBK1 by directly binding to TBK1 [ 64 ]. Additionally, we uncovered previously unknown interactions with host kinases, such as the interaction between Nsp12 and TLK1 ( Figure 4 B).…”
Section: Resultsmentioning
confidence: 99%